Niosomes encapsulated in biohydrogels for tunable delivery of phytoalexin resveratrol - Machado, Noelia Daiana (2019)
A series of biohydrogels based on mixtures of kappa-carrageenan (κ-carrageenan, κ-C) and gelatin were evaluated as potential soft delivery vehicles for the encapsulation and subsequent release of non-ionic surfactant vesicles (niosomes) loaded with resveratrol (RSV). The niosomes were prepared using a mixture of amphiphilic lipids Tween 80 and Span 80 in water. The results showed that RSV-niosomes did not significantly affect the hydrogelation properties of the biopolymer mixture. Moreover, in vitro drug release experiments from biohydrogels containing RSV-niosomes were successfully carried out under simulated gastrointestinal conditions. The RSV-niosomal liberation profiles from hydrogels were fitted using first order kinetics, Higuchi, Korsmeyer-Peppas and Weibull drug release models, showing the prevalence of diffusion mechanisms in each case. In addition, the RSV release was easily tuned by adjusting the total concentration of κ-C : gelatin. Interestingly, the niosomal-hydrogel system was also found to prevent the trans-to-cis photoisomerization of RSV.